1994
DOI: 10.1161/01.str.25.3.582
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patent foramen ovale associated with cryptogenic stroke. A biplane transesophageal echocardiographic study.

Abstract: Background and Purpose Patent foramen ovale is associated with ischemic stroke in patients without a clearly identifiable etiology for stroke (cryptogenic stroke). Paradoxical embolization is thought to be a potential mechanism. However, patent foramen ovale is also found in patients with known cause of stroke. Therefore, using contrast transesophageal echocardiography, we characterized the patent foramen ovale in cryptogenic stroke patients to assess morphological factors that may contribute to paradoxical em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
1
5

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(161 citation statements)
references
References 34 publications
8
142
1
5
Order By: Relevance
“…28 The size and the degree of shunt appear to be important in determining the significance of PFO. [15][16][17][18] In this study, with a large number of prospectively studied patients, we also confirm that larger PFOs are associated with cryptogenic stroke. We demonstrate that when the stroke patients are treated medically, the rate of recurrent stroke or death is similar between patients with and without PFO.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…28 The size and the degree of shunt appear to be important in determining the significance of PFO. [15][16][17][18] In this study, with a large number of prospectively studied patients, we also confirm that larger PFOs are associated with cryptogenic stroke. We demonstrate that when the stroke patients are treated medically, the rate of recurrent stroke or death is similar between patients with and without PFO.…”
Section: Discussionsupporting
confidence: 82%
“…24,25 PFO size was determined by use of a caliper on a video frame demonstrating the maximum separation of the septum primum from the septum secundum. 15, 17 The number of microbubbles was counted from a video frame demonstrating the maximum number on a video frame within 3 cardiac cycles from the opacification of the right atrium. 15,17,24,25 PFOs with Ն2 mm separation of the septum secundum and primum or with Ն10 microbubbles appearing in the left atrium were classified as large, and all other PFOs as small.…”
Section: Analysis Of Tapesmentioning
confidence: 99%
See 1 more Smart Citation
“…Homma et al 25 identified other risk factors: (1) the presence of a Eustachian valve directed toward the PFO ( Figure 3); (2) the gaping diameter of the PFO; and (3) the number of micro-bubbles present in the left atrium during the first seconds after release of a Valsalva maneuver during a bubble test.…”
Section: Rationale For Pfo Closure In Stroke Patientsmentioning
confidence: 99%
“…This situation threatened these young adults as was demonstrated at the start of the 1990s in retrospective studies by COMESS et al [8], STONE et al [9] (8.4%), MAS & ZUBER [10] (3.4%) and prospective studies by BOGOUSSLAVSKY [11] (3.8%). These ratifications led several authors (DI TULLIO et al [12], CABANES et al [13] and HOMMA et al [14] to define to what extent the anatomical structures of the interatrial septum could be implicated in embolic events. This aspect is of fundamental importance for the stratification of recurrence risk of strokes or TIA until the present time.…”
Section: Introductionmentioning
confidence: 99%